APA YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI OBYEK WISATA MATA AIR COKRO - Meita Yulisma Wardani; Arif Farida (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to determine the effect of merchant income on tourist attractions with case studies conducted at the Cokro Springs object. The type of data used is primary data using a saturated sample of 64 respondents. The method of analysis of this research uses multiple regression analysis using SPSS version 25 and the data collection method uses a questionnaire. The results showed that business capital partially had an effect on income, working hours partially had an effect on income, and the number of visitors partially had an effect on income. The results of the F test show a Sig value of 0.000, less than 0.05, meaning that the independent variables of business capital, working hours, and the number of visitors together have a significant effect on the income of traders at the Cokro Springs tourist attraction..